2014
DOI: 10.1074/jbc.m114.613901
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Specificity of Lysine Acetyltransferases

Abstract: Background: Gcn5-related N-acetyltransferases (GNATs) modify proteins in all domains of life. Results: The structure of a GNAT was determined in complex with a protein substrate. Conclusion: Specificity of the GNAT-protein interaction is dictated by an extensive interaction surface compared with GNATpeptide structures. Significance: This is the first structure of a GNAT-protein acetylation complex, and it may enable structure-based identification and engineering of GNAT substrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…Briefly, results obtained from in vitro and in vivo analyses of single-amino-acid SePat variants showed that such variants had low enzymatic activity (70). Furthermore, results from recently reported structural work aimed at understanding the substrate specificity of Pat enzymes suggested that in the absence of the large domain of Pat, the catalytic domain of the enzyme inefficiently interacts with its protein substrate (71). Whatever the role of the N-terminal domain may be, it is likely to also play a role in sensing acetyl-CoA.…”
Section: Bacterial Gcn5-related N-acyltransferasesmentioning
confidence: 99%
See 3 more Smart Citations
“…Briefly, results obtained from in vitro and in vivo analyses of single-amino-acid SePat variants showed that such variants had low enzymatic activity (70). Furthermore, results from recently reported structural work aimed at understanding the substrate specificity of Pat enzymes suggested that in the absence of the large domain of Pat, the catalytic domain of the enzyme inefficiently interacts with its protein substrate (71). Whatever the role of the N-terminal domain may be, it is likely to also play a role in sensing acetyl-CoA.…”
Section: Bacterial Gcn5-related N-acyltransferasesmentioning
confidence: 99%
“…These SePat homologues are comprised of two distinct domains, a large (ϳ700-residue) N-terminal domain and the catalytic GNAT domain (ϳ200 residues) at the C terminus (68,69). Although the function of the large N-terminal domain of Pat enzymes remains largely unclear, insights into its relevance to Pat function have been reported (70,71). Briefly, results obtained from in vitro and in vivo analyses of single-amino-acid SePat variants showed that such variants had low enzymatic activity (70).…”
Section: Bacterial Gcn5-related N-acyltransferasesmentioning
confidence: 99%
See 2 more Smart Citations
“…6B). In fact, it has been demonstrated that full-length SePat is necessary for efficient binding to acetyl-CoA (8) and that the specificity of the GNAT-protein interaction is dictated by an extensive interaction surface (66). Moreover, the tetramer PatZ Acs-like could not be acetylated by PatZ WT (Fig.…”
Section: Patz Activity Is Controlled By Positive Cooperativity and Acsmentioning
confidence: 95%